HLA alleles, COVID-19 vaccine antibody response and real-world breakthrough outcomes - Xie, J; Mothe, B; Herraiz, MA; Li, C; Xu, Y; Jödicke, AM; Gao, Y; Feng, S; Wei, J; Chen, Z; Hong, S; Wu, Y; et al. (2023)
The rapid development, approval, and global distribution of COVID-19 vaccines represent an unprecedented intervention in public health history, with over 13 billion doses administered worldwide in two years. However, our understanding of the HLA genetic underpinnings of COVID-19 vaccine-induced antibody responses and their clinical implications for breakthrough outcomes remain limited. To bridge this knowledge gap, we designed and performed a series of genetic and epidemiological analyses among 368,098 vaccinated individuals, and a subset of 194,371 participants who had antibody serology tests. Firstly, we corroborated earlier findings that SNPs associated with antibody response were predominantly located in Major Histocompatibility Complex region, and that the expansive HLA-DQB106 allele family was linked to better antibody responses. However, our findings contest the claim that DQB106 alleles alone significantly impact breakthrough risks. Additionally, our results suggest that the specific DQB106:04 subtype could be the true causal allele, as opposed to the previously reported DQB106:02. Secondly, we identified and validated six new functional HLA alleles that independently contribute to vaccine-induced antibody responses. Moreover, we unravelled additive effects of variations across multiple HLA genes that, concurrently, change the risk of clinically relevant breakthrough COVID-19 outcomes. Finally, we detangled the overall vaccine effectiveness and showed that antibody positivity accounts for approximately 20% protection against breakthrough infection and 50% against severe outcomes. These novel findings provide robust population evidence demonstrating how variations within HLA genes strongly, collectively, and causally influence vaccine-induced antibody responses, and the risk of COVID-19 breakthrough infection and related outcomes, with implications for subsequent functional research and personalised vaccination.